Digital Learning Innovation : Language Collaboration In Tanjungmojo Village - Azzahra, Silmameila Ishma; Elmumtaza, Safira; Saniyyah, Zayyinatus; Izzatunnisa, Syakhna; Azizi, Muhammad Maulana; Jasmine, Annisa Sekar; Zahrok, Jihan Fatimatu; Aras, M. Iffat Althaaf; Khasanah, Rita Ariyana Nur (PT. Amirul Bangun Bangsa, 2024)
This research aims to develop digital learning innovation through language collaboration in Tanjungmojo Village, where low digital literacy and limited access to quality educational resources are the main problems. Limited foreign language skills among village communities are also an obstacle in keeping up with developments in global technology and communication. To overcome this challenge, the research uses an action research approach by involving the active participation of local communities in the development of digital-based foreign language learning programs. This research was conducted in three main stages: (1) analysis of local needs and potential, (2) development and implementation of a language-based digital learning program, and (3) evaluation of the effectiveness of the program. Data was collected through interviews, participant observation, and questionnaires filled out by program participants and the general public. The research results show that the digital learning program developed succeeded in significantly increasing the participants' digital literacy and foreign language skills. In addition, collaboration between local communities and teaching staff creates an inclusive and sustainable learning environment.The main trends identified in this research include increasing community participation, especially teenagers and young adults, in learning activities, as well as increasing interest in continuing to learn and develop new skills through digital platforms. This research also highlights the importance of community support and technology accessibility for the success of learning programs in rural areas. The MIT-18 KKN program in Tanjungmojo Village involved 97 students with learning methods through bilingual digital films and group discussions, which encouraged high participation and involvement. Despite challenges in content retention and technical limitations, this initiative shows great potential in improving education in rural areas and bridging the existing educational gap.